Epistemic Justice in the Blue Economy: Recognizing Coastal Women’s Knowledge for Inclusive and Sustainable Ocean Development - Anindya; Angkita Mulyawisdawati, Richa (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2025)
Women are central to sustaining the blue economy, yet their ecological knowledge is often marginalized in coastal development policies. This exclusion reflects a form of epistemic injustice, revealing a sharp contradiction between women’s vital role in ecological sustainability and the failure of policy frameworks to acknowledge their contributions. This study seeks to analyze the forms of epistemic injustice experienced by coastal women and the sustainable practices they pursue, while proposing an alternative and more inclusive framework grounded in the principles of Islamic economic. This study employs a qualitative critical-interpretive approach using a systematic review of academic literature, policy documents, and case studies from coastal communities engaged in Blue Economy initiatives. Data are thematically analyzed to uncover patterns of epistemic injustice, the marginalization of women’s knowledge systems, and opportunities for more inclusive and sustainable ocean governance. Based on field data, coastal women experience multiple forms of epistemic injustice, ranging from the undermining of their credibility when sharing knowledge, difficulties in articulating their lived experiences, to limited participation in decision-making processes. These findings highlight that, despite their vital contributions to marine resource management and the Blue Economy, their knowledge and voices remain systematically marginalized by social structures and local power hierarchies. In Islamic economics, epistemic justice in the blue economy reflects al-‘adl (justice) and al-musāwah (equality), ensuring that local knowledge especially women’s experiences are recognized and taken into account in policy-making. This study concludes that coastal women face systemic epistemic injustice in the Blue Economy, implying the urgent need for gender-responsive and Sharia-based frameworks that recognize their knowledge to achieve al-maslahah and truly just maritime development. Sustainable ocean governance cannot be achieved without centering women’s knowledge and agency as a foundation of epistemic justice in the Blue Economy.